The perceptions of undergraduate students toward reading contemporary fiction in English: a case study of content-based ESL instruction at a self-financed tertiary institution in Hong Kong - Lo, Noble; Shi, Huiwen (Frontiers in Education, 2024)
The study explores the effectiveness of teaching English literature to Hong Kong undergraduate students, particularly in a general education course titled "Fiction and Life: Understanding Human Development." This course marked the first exposure for students to book-length fiction in English and critical response written in English, revealing the efficacy of using fictional works as contentbased ESL instruction at the tertiary level in Hong Kong. Employing a mixed-methods approach, the study included questionnaires distributed to 310 students and thematic analysis of semi-structured interview data. Findings indicate a largely positive attitude toward the reading and writing experience, suggesting benefits for ESL teaching and learning in Asia. The study advocates for incorporating English literature into the general education curriculum to foster a more organic and contextualized language acquisition process. This research uniquely contributes to the field by examining student perceptions in a self-financed tertiary institution context, offering new insights that have not been explored before in Hong Kong's ESL landscape.